School Based Religious Education in Practice: Evaluating the Sekolah Mengaji Program - Sipa Nurhayati; Ulfah; Endi Suhendi (Journal of Teacher Training and Educational Research, 2025)
The Sekolah Mengaji Program is a religious education policy initiated by the Bandung Regency Government as a mandatory local content subject in elementary and junior high schools. This study aims to analyze the implementation of the Sekolah Mengaji Program at SMP Negeri 1 Cangkuang, focusing on the planning, execution, and evaluation stages. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, direct observation, and document analysis, involving the principal, Islamic education teachers, guru mengaji, and students. The findings indicate that the program was systematically and collaboratively planned, with strong coordination between school stakeholders and teaching staff. Implementation included reading, writing, and memorizing the Qur’an (BTHQ), adapted to students’ proficiency levels. Although traditional teaching methods dominate, teachers demonstrated responsive adaptation to students' needs. Evaluation was conducted periodically through progress monitoring and documentation of student achievements. The study concludes that the program has been effectively managed, yet further improvements are needed in instructional innovation and teacher capacity-building to enhance its overall impact.